Involvement of Transcription Elongation Factor GreA in Mycobacterium Viability, Antibiotic Susceptibility, and Intracellular Fitness - Feng, Siyuan; Liu, Yan; Liang, Wanfei; El-Sayed Ahmed, Mohamed Abd El-Gawad; Zhao, Zihan; Shen, Cong; Roberts, Adam P.; Liang, Lujie; Liao, Liya; Zhong, Zhijuan; Guo, Zhaowang; Yang, Yongqiang; et al. (Frontiers in Microbiology, 2020)
There is growing evidence that GreA aids adaptation to stressful environments in various bacteria. However, the functions of GreA among mycobacteria remain obscure. Here, we report on cellular consequences following deletion of greA gene in Mycobacterium spp. The greA mutant strain (ΔgreA) was generated in Mycobacterium smegmatis, Mycobacterium tuberculosis (MTB) H37Ra, and M. tuberculosis H37Rv. Deletion of greA results in growth retardation and poor survival in response to adverse stress, besides rendering M. tuberculosis more susceptible to vancomycin and rifampicin. By using RNA-seq, we observe that disrupting greA results in the differential regulation of 195 genes in M. smegmatis with 167 being negatively regulated. Among these, KEGG pathways significantly enriched for differentially regulated genes included tryptophan metabolism, starch and sucrose metabolism, and carotenoid biosynthesis, supporting a role of GreA in the metabolic regulation of mycobacteria. Moreover, like Escherichia coli GreA, M. smegmatis GreA exhibits a series of conservative features, and the anti-backtracking activity of C-terminal domain is indispensable for the expression of glgX, a gene was down-regulated in the RNA-seq data. Interestingly, the decrease in the expression of glgX by CRISPR interference, resulted in reduced growth. Finally, intracellular fitness significantly declines due to loss of greA. Our data indicates that GreA is an important factor for the survival and resistance establishment in Mycobacterium spp. This study provides new insight into GreA as a potential target in multi-drug resistant TB treatment.